The Management of the Beach-Cast Seagrass Wracks—A Numerical Modelling Approach - Andrea Cucco; Giovanni Quattrocchi; Walter Brambilla; Augusto Navone; Pieraugusto Panzalis; Simone Simeone (Journal of Marine Science and Engineering, 2020)
Seagrass wrack are commonly found on the beach face of the sandy shore all around the world and often persists in situ during the whole year, favouring the emergence of conflicts for the use of the sandy coasts for bathing or for other recreational purposes. As a consequence, these deposits are often removed from the beach during the summer months, temporary stocked, and relocated on the shore face in the next autumn or winter season. The selection of the sites on the shoreline where the leaves should be released before the storms season is often an issue, considering the optimization needs between the transportation costs and the oceanographic features of the dumping site. In this study, a numerical approach was proposed to identify the most suitable areas for the autumnal repositioning of the seagrass wracks for two beaches of Sardinia, an island located in the Western Mediterranean Sea where Posidonia oceanica (L. Delile, 1813) is the most widespread seagrass species. The method is based on the use of hydrodynamic, wave, and particle tracking models and provides important indications useful for the management of this type of practice that can be extended to all different type of beaches along the Mediterranean coasts.